Kandungan Indeks Glikemik Dan Beban Glikemik Beras Lokal Hanyar Dan Usang - zulfiana dewi; sajiman sajiman (Jurnal Skala Kesehatan, 2021)
The prevalence of Diabetes Mellitus (DM) in South Kalimantan Province increased from 1.0% in 2007 to 1.4% in 2013. Low Glycemic Index (IG) foods can improve insulin sensitivity and also increase sugar efficiency, and increase DM efficiency. The purpose of this study is to publicize the differences between the Glycemic Index and the Glycemic Load in local rice. This type of experiment research. The expected data obtained is the value of the Glycemic Index and Glycemic Load. The design in this study is Post-only Control Group Design using controls without random assignment. The results of the glycemic index test obtained the highest IG value in rice from karang dukuh usang by 120.31%, and the lowest in rice from Unus Hanyar rice is equal to 87.15%. The results of glycemic load obtained the highest BG value in rice from karang dukuh usang rice is equal to 25.75%, and the lowest in rice from karang dukuh hanyar rice that is equal to 19.26. The conclusion in this study is the difference in the glycemic index and the glycemic load on rice from floating and obsolete local rice Keyword : Glycemic Index; Glycemic load; Local Usang Rice; Local Hanyar Rice.